THE ORIGIN OF THE HADITH ABOUT JAMPI-JAMPI: A Review of Harald Motzki's Isnad Cum Matan Analysis - Syaiful, Muhammad; Masuwd, Mowafg Abrahem (RIWAYAH, 2025)
Hadiths concerning conjuring or ruqyah constitute a significant theme in hadith studies, particularly regarding issues of authenticity in both isnād and matn. Divergent perspectives between classical and modern scholars on the validity of these traditions underscore the necessity for a more nuanced and critical analysis. This study investigates the origin and transmission of the jampi-jampi (incantation) hadiths using the isnād-cum-matn analytical framework pioneered by Harald Motzki. Employing a qualitative methodology through literature-based research, data were sourced from canonical hadith collections such as Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, and Sunan Abī Dāwūd, along with contemporary scholarship in hadith criticism. Through descriptive-analytical techniques, this study maps the transmission chains (asānīd), evaluates narrator reliability, and compares textual variants of the matn. The findings reveal that while variations exist in wording, the jampi-jampi hadiths possess multiple strong lines of transmission. Motzki’s method proves instrumental in uncovering the historical strata of hadith development, demonstrating that the majority of ruqyah-related traditions can be traced reliably to the generation of the tābi‘īn. This study contributes to the field of hadith methodology by reinforcing the importance of integrated textual and transmission analysis and offers deeper contextual insight into the normative role of ruqyah within Muslim religious practice.[Hadis-hadis tentang jampi atau ruqyah merupakan tema penting dalam studi hadis, khususnya dalam hal keotentikan baik dari sisi sanad maupun matan. Perbedaan pandangan antara ulama klasik dan sarjana modern terkait validitas hadis-hadis tersebut menunjukkan perlunya kajian yang lebih mendalam dan kritis. Penelitian ini mengkaji asal-usul dan transmisi hadis jampi-jampi dengan menggunakan pendekatan isnād-cum-matn yang dikembangkan oleh Harald Motzki. Dengan metode kualitatif melalui studi pustaka, data diperoleh dari kitab-kitab hadis kanonik seperti Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, dan Sunan Abī Dāwūd, serta literatur kritik hadis kontemporer. Melalui teknik analisis deskriptif-analitis, penelitian ini memetakan jalur transmisi (asānīd), menilai kredibilitas para perawi, dan membandingkan varian teks (matan) hadis. Hasil penelitian menunjukkan bahwa meskipun terdapat perbedaan redaksi, hadis-hadis jampi-jampi memiliki beberapa jalur transmisi yang kuat. Pendekatan Motzki terbukti efektif dalam mengungkap lapisan-lapisan historis dalam perkembangan hadis, serta menunjukkan bahwa sebagian besar tradisi tentang ruqyah dapat ditelusuri secara andal hingga generasi tābi‘īn. Studi ini memberikan kontribusi pada metodologi ilmu hadis dengan menegaskan pentingnya analisis integratif antara teks dan transmisi, serta menawarkan pemahaman kontekstual yang lebih mendalam terhadap peran normatif ruqyah dalam praktik keagamaan umat Islam.]